Pelatihan Pengolahan Kerang menjadi Kuliner Khas Banjar Kemuning di Desa Banjar Kemuning Kecamatan Sedati Kabupaten Sidoarjo: Pelatihan Pengolahan Kerang menjadi Kuliner Khas Banjar Kemuning - Medya Ayunda Fitr; Rina Sri Wulandari; Zahrotul Azizah; Laily Noer Hamidah; Listin Fitrianah (Universitas Nahdlatul Ulama Sidoarjo, 2022)
Scallops are one of the marine products that are usually caught by fishermen.Shellfish generally contain protein, minerals, vitamins, and omega 3 fatty acids. This highnutritional content makes shellfish processed into various types of food. Banjar KemuningVillage is one of the areas where the people work as fishermen where shellfish are acommon catch. The catch is sold to middlemen or to the people of Banjar KemuningVillage. In addition, the catch of shellfish is also managed to become a favorite culinaryform of shellfish satay by the community. Variations in the processing of shellfish are madeto add to the treasures of culinary diversity that is produced as a special food of BanjarKemuning Village. Scallops are used as additional ingredients for pentol and tempura toadd nutritional value and attractiveness. In addition, this food can add opportunities toimprove the community's economy.